2006
DOI: 10.1080/01485010500315479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight on Testosterone/Estradiol Ratio in Oligozoospermic Patients

Abstract: To evaluate the effect of body mass on the hormonal and semen profiles of subfertile men with oligozoospemia, sperm concentration and reproductive hormone levels were compared in two body mass index (BMI) groups: underweight or normal weight patients (BMI = 25 kg/m2) vs. overweight or obese patients (BMI > 25 kg/m2). The mean BMI was 27 +/- 4.6 kg/m2. The testosterone/estradiol ratio was significantly reduced in the high BMI group as compared to the low BMI group (17 +/- 4 vs. 12 +/- 3; p < 0.05). A similar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 18 publications
(19 reference statements)
4
69
3
8
Order By: Relevance
“…Aromatase is expressed in the intercellular septa of fat tissue and converts testosterone to 17β-estradiol. 10 Obesity is one of the causes of secondary hypogonadism (Box 1). In obese men, increased adipose tissue results in increased aromatase activity and a relative elevation in estradiol levels, which inhibits gonadotropin secretion from the pituitary.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%
“…Aromatase is expressed in the intercellular septa of fat tissue and converts testosterone to 17β-estradiol. 10 Obesity is one of the causes of secondary hypogonadism (Box 1). In obese men, increased adipose tissue results in increased aromatase activity and a relative elevation in estradiol levels, which inhibits gonadotropin secretion from the pituitary.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%
“…It has been shown that the elevated BMI of men results in decreased fecundity (Sallmen et al, 2006;Ramlau-Hansen et al, 2007). To interpret the reduced fertility of obese men, studies have investigated the relationship between obesity and semen quality (Fejes et al, 2005;Levitas et al, 2007;Hammoud et al, 2008;Pauli et al, 2008;Martini et al, 2010;McDonald et al, 2010). The results are conflicting.…”
Section: Introductionmentioning
confidence: 87%
“…When it comes to endocrine factors, the following are linked to components of the metabolic syndrome: hyperinsulinaemia, 13 an increased level of oestradiol, 30 a reduced level of testosterone, 31,32 a reduced testosterone/oestradiol quotient 33 and a reduced level of SHBG. 34 All these endocrine aberrations, with the exception of a reduced testosterone level, which did not reach statistical significance, were linked to BPH as measured by the total prostate gland volume in the present report.…”
Section: Discussionmentioning
confidence: 99%